Land-cover changes and microclimate risks around Yogyakarta International Airport - R. Muhammad Syarif Abdurrahman; R. Yosi Aprian Sari (Universitas Negeri Yogyakarta, 2026)
International airport infrastructure development triggers complex spatial transformations with implications for the balance of regional ecosystems. This study analyzes land-cover change dynamics, surface temperature distribution, vegetation conditions, and microclimate risk zones in the Yogyakarta International Airport (YIA) area using Landsat 8 imagery processed on the Google Earth Engine platform. Methods include Random Forest classification for land cover mapping, Land Surface Temperature (LST) analysis, Normalized Difference Vegetation Index (NDVI) extraction, and Vegetation Stress Index (VSI) compilation as ecological pressure indicators. Results show a 27.2% expansion of forest cover and a 30.4% reduction in water bodies during 2015–2024, contrasting with conventional urban sprawl theory. Surface temperature increased across all land cover classes except built-up areas, which decreased by 2.85°C, with Urban Heat Island formation extending to a radius of 5–7 km. Findings introduce green intensification as a novel reforestation pathway driven by the internalization of mitigation obligations within infrastructure project design. This phenomenon challenges conventional theoretical assumptions and extends existing forest transition frameworks to tropical infrastructure contexts.